2016
DOI: 10.1080/10447318.2016.1243928
|View full text |Cite
|
Sign up to set email alerts
|

A Textual Feedback Tool for Empowering Participants in Usability and UX Evaluations

Abstract: The usability movement has historically always sought to empower end-users of computers, so that they understand what is happening and can control the outcome. In this paper, we develop and evaluate a 'Textual feedback' tool for usability and UX evaluation that can be used to empower welleducated, but low-status, users in UX evaluations in countries and contexts with high power distances. The proposed tool contributes to the HCI community's pool of localized UX evaluation tools. We evaluate the tool with 40 us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
5
0
2
Order By: Relevance
“…Sivaji et al [50] found that also gender has an effect on the effectiveness of a method used in usability evaluation, in particular when gender interacts with the social status of the users performing the evaluation.…”
Section: 4mentioning
confidence: 99%
“…Sivaji et al [50] found that also gender has an effect on the effectiveness of a method used in usability evaluation, in particular when gender interacts with the social status of the users performing the evaluation.…”
Section: 4mentioning
confidence: 99%
“…Esta área se preocupa con el diseño, evaluación e implementación de sistemas computacionales interactivos para el uso humano. Así, como en el estudio de los principales fenómenos de uso (Hewett, 1996;Sivaji, Nielsen, Clemmensen, 2017).…”
Section: Interacción Humana Con El Computadorunclassified
“…However, in order to be able to effectively monitor, measure and effectively apply this information to product development and subsequent iterations, many specialized disciplines are required. It is these different disciplines that are covered by one overarching term, called UX (Sivaji, et al, 2016).…”
Section: Introduction User Experiencementioning
confidence: 99%